Fitness costs of susceptible and resistant radish biotypes to ALS-inhibitor herbicides - Cechin, Joanei; Vargas, Leandro; Agostinetto, Dirceu; Zimmer, Vinicius; Pertile, Mariane; Dal Magro, Taisa (Comunicata Scientiae, 2018)
Radish is an important weed that causes yield reduction in winter crops in southern Brazil. The control chemical of radish is an important and essential step to prevent damage on crops. However the intensive use of ALS-inhibitors herbicides favors the selection resistant biotypes. The selection can influence the adaptive traits of biotypes with physiological changes and growth variables and plant reproduction. The objective of the study was compare the fitness costs of susceptible and resistant radish biotypes to ALS-inhibitors herbicides. The experiment was conducted in greenhouse using completely randomized design with five replications. The treatments were arranged in factorial arrangement corresponding to susceptible and resistant biotypes (B1 and B4) and nine sampling times (14, 28, 42, 56, 70, 84, 98, 112 and 126 days after emergency), respectively. The variables evaluated were plant height, shoot dry matter, root dry matter, total dry matter, leaf area, growth rate, relative growth rate, leaf area ratio, number of siliques and seeds produced per plant. The results showed that the resistant biotype (B4) had no fitness costs when compared to the susceptible biotype (B1).